2019
DOI: 10.18203/2349-3291.ijcp20192041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of neonatal thrombocytopenia in a tertiary care hospital

Abstract: Background: Thrombocytopenia (platelet count <1,50,000/µL) is one of the most common haematological problems in neonatal intensive care units. In contrast, only 2% of the normal neonates are thrombocytopenic at birth with severe thrombocytopenia (platelet count <50,000/µL) occurring in less than 3/1000 term infants. Multiple disease processes can cause thrombocytopenia in neonates. The important causes of thrombocytopenia in neonates are sepsis, birth asphyxia, prematurity, intra-uterine growth retardati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
3
3
2
Order By: Relevance
“…8 Regional data from India found 46% of neonates with TCP in NICU to have mild TCP while 35% had moderate TCP while 19% were having severe TCP. 12 These findings from India are relatively similar to what has been shown in this research. Khalessi N and colleagues as well as Ghamdi AM et al also reported somewhat similar distribution of TCP among neonates in NICU.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…8 Regional data from India found 46% of neonates with TCP in NICU to have mild TCP while 35% had moderate TCP while 19% were having severe TCP. 12 These findings from India are relatively similar to what has been shown in this research. Khalessi N and colleagues as well as Ghamdi AM et al also reported somewhat similar distribution of TCP among neonates in NICU.…”
Section: Resultssupporting
confidence: 89%
“…2,15 As we know, sepsis might be leading to TCP because of relatively lower production of platelets and higher rates of destruction; these could be the reasons behind this exaggerated proportion of sepsis and its linkage with TCP in this study. 12 Some others have shown sepsis as well as birth asphyxia to have significant linkage with neonatal TCP but we did not find any significant connection of birth asphyxia with TCP in this study. 2,5 This study had some limitations as well.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…Etiological profile in the present study showed 36 (42.3%) cases presenting with neonatal septicemia as the most Meena SL et al [2] and Kripa Nath Mishra et al [1]. According to Jeremiah et al [13], birth asphyxia (33.3%) was most common which is followed by jaundice (19.7%).…”
Section: Discussionmentioning
confidence: 48%
“…It increases mortality, especially in septicemic cases. Multiple disease processes cause thrombocytopenia in neonates and these are classified as early-onset (<72 hours) and late-onset (>72 hours) neonatal thrombocytopenia [2].…”
Section: Introductionmentioning
confidence: 99%